The Relationship Of Repetion And The Budaiya Science In Modern Poerty - .ADJADJ, ABDELMOUMENE; Toul, Mohamed (El Omda in Linguistics and Discourse Analysis, 2024)
Abstract: Repetition is an aesthetic technique that has left its mark in poetry, it has enriched the poems, it has a relation with the science of Budaiya, it intersects with him, so it is the source and target of repetition. The target of this research is to identify the repetition and its relationship to the science of Budaiya. The study indicated the role that repetition plays. The methodology in this research represented the study of repetition and its relationship to the science of Budaiya; So that included many types, which is it’s required to reach the main results that the original types have a strong relationship with repetition in the modern era.